COMMERCIAL DOCUMENTS FROM THE CAIRO GENIZA DURING THE AYYUBID PERIOD (569-648 AH / 1173-1250 AD) - Ahlam Salman Ali Al-Janabi; Dr. Abdul-Jabbar Mahmoud Shreims (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The Cairo Geniza documents are one of the sources of the history of the Islamic world, especially the economic one. There are many documents that confirm and refer to the activity of economic life and the role of the Jews in Egypt and neighboring countries during the Ayyubid era (569-648 AH / 1173-1250 AD); Therefore, the meaning of the Geniza or Genizah and its concept, linguistically and idiomatically, was clarified, and then the role of the geographical location of Egypt in stimulating and encouraging merchants of internal and external trade was found. And what was exported to countries and what was imported, their weights, colors, quantities and prices, and from the sender and the addressee, all of that was found. Preserved with lists, records and documents of the Geniza, and it was concluded that the Ayyubid economy in general and trade in particular was in the most beautiful form, providing security and all the requirements of successful trade despite the political instability thanks to the firmness, strength and rationality of the Ayyubid authority at the time.